In vivo generation of a mature and functional artificial skeletal muscle. Issue 4 (25th February 2015) - Fuoco, Claudia; Rizzi, Roberto; Biondo, Antonella; Longa, Emanuela; Mascaro, Anna; Shapira‐Schweitzer, Keren; Kossovar, Olga; Benedetti, Sara; Salvatori, Maria L; Santoleri, Sabrina; Testa, Stefano; Bernardini, Sergio; et al.
<x xml:space="preserve">Abstract</x> This study proposes a novel and efficient strategy for skeletal muscle tissue engineering based on in vitro mixing of mouse or human mesoangioblasts with a PEG‐fibrinogen, which promotes their survival and differentiation into muscle.<boxed-text content-type="graphic" id="emmm201404062-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>